Analisis Energi Gas Engine Siklus Otto Kapasitas 835 KW - Syaifudin, Ahmad; Romy, Romy; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Biogas from Palm Oil Mill Effluent (POME) is one of renewable energy resources that can be used to reduce theuse of fossil energy in satisfying the electricity needs. At biogas power plant, gas engine is an importantcomponent which functions to convert the energy contained biogas into mechanical energy to drive the electricgenerator. Because of its important function, the performance of the gas engine needs to be maintained in orderto remain well operated. In addition to maintaining the performance of gas engine, steps in improving theefficiency of gas engine energy usage also need to be done in order to become more efficient. Efficiency of thegas engine depends on the overall efficiency of cylinders gas engine in order to convert the energy of fuel intowork. Energy analysis is needed to know the efficiency of multi-cylinder gas engine at biogas power plant, so itcan be known the gas engine performance and can be used for further analysis in increasing the efficiency of theuse of renewable energy sources (biogas) in gas engine. The purpose of this research was to know the energy orthermal efficiency of gas engine. Variables used in the analysis were a composition of biogas, flow rate ofbiogas, a temperature of gas mixture entering the gas engine and temperature of exhaust gas. The energyanalysis result showed that the efficiency of all cylinders varies and the greatest energy or thermal efficiency ofgas engine is on 5th and 10th cylinder (56.29%) and lowest in 8th cylinder (56.17%). The average energy orthermal efficiency of gas engine is 56.23%.Keyword : Biogas, Biogas Power Plant, Gas Engine, Otto Cycle, Energy Analysis